La inducción embrionaria en Sócrates - Orozco Livia, Víctor (2009)
The first proposal for an orderly way of thinking about seeking the truth, is a merit that belongs to the greek philosopher Socrates. Socrates in his time represents the highest intellectual virtue of greek thinkers, arising under the magnificence of Athens in the middle of V century bc, wich occurred after several social events, politicians and intellectuals in the context of a slave regimen that tended to accentuate their features. It happened that the fal of the Areopagus who was the center of the elitist and conservative aristocracy opened a more democratic space for citizens, the military victory of Greece against the Persians expand trade and cultural exchanges by Athens with the most important cities of the time, and dispute with the sophists by Socrates about the truth, and so on, were some of the converting factors that influenced the ideas of Socrates. Amid such delopments Socrates proposed an initial induction method.